Effect of engine oil additives reduction on the tribofilm structure of a cylinder liner model surface. Issue 4 (22nd July 2019) - Miranda-Medina, Maria de Lourdes; Tomastik, Christian; Truglas, Tia; Groiss, Heiko; Jech, Martin
Abstract : Purpose: The purpose of this paper is to provide a general picture for describing the formed tribofilm, including chemical and physical aspects in the micro-scale and the nano-scale. In a previous study, the durability of zinc dialkyl dithiophosphate (ZDDP) tribofilms on cylinder liner samples has been investigated in a tribometer model system by using fresh and aged fully formulated oils and replacing them with PAO8 without additives. Analyses of the derived tribofilms by means of X-ray photoelectron spectroscopy and scanning electron microscopy could give some hints about the underlying mechanisms of the tribofilm build-up and wear performance, but a final model has not been achieved. Design/methodology/approach: Thus, characterisation of these tribofilms by means of focused ion beam-transmission electron microscopy (FIB-TEM) and energy dispersive X-ray spectroscopy is presented and a concluding model of the underlying mechanisms of tribofilm build-up is discussed in this paper. Findings: For tribotests running first with fresh fully formulated engine oil, a rather homogeneous ZDDP-like tribofilm is found underneath a carbon rich tribofilm after changing to non-additivated PAO8. However, when the tests run first with aged fully formulated engine oil, no ZDDP-like tribofilm has been found after changing to non-additivated PAO8, but a wear protective carbon rich tribofilm. Originality/value: The obtained results provide insights into the structure and durability of tribofilms. Carbon-based tribofilms are built up on the basis of non-additivated PAO8 because of the previously present ZDDP tribofilms, which suggests an alternative way to reducing the consumption of antiwear additives.